Constructing standards of classroom mathematics teacher behavior that support the creative thinking of his students in the preparatory stage / scientific branch (Journal of the College of Basic Education, 2022)
The aim of the research is to build standards of behavior of the classroom teacher of mathematics that support the creative thinking of his students in the preparatory stage / the scientific branch.The first axis - directing classroom questions that support creative thinking, contains (11) sub-skills.The second axis - the teacher's response supporting creative thinking, contains (9) sub-skills.The third axis - building an exciting classroom environment for creative thinking, and contains (17) sub-skills.In light of the current research objective, its limitations and results,